A Survey of Social Media Use and Preferences in Patients with Inflammatory Bowel Disease. Issue 11 (November 2016) - Reich, Jason; Guo, Ling; Hall, Julia; Tran, Ashley; Weinberg, Janice; Groshek, Jacob; Rowell, Tanya E.; DiPalma, Jack A.; Farraye, Francis A.
Abstract : Background: With the recent increase in the use of social media, patients with chronic illnesses are using the Internet as a resource for disease management. As the peak incidence of inflammatory bowel disease (IBD) occurs in patients between the ages of 15 and 30, IBD is a suitable condition to study social media use. The aim of this study was to assess social media usage and preferences in patients with IBD. Methods: We administered a survey to 118 patients with IBD at our outpatient practice at the Boston Medical Center (BMC), Center for Digestive Disorders, and the University of Southern Alabama (USA) between November 1, 2015, and March 9, 2016. Results: The most frequently used IBD-specific social media website was the CCFA (86%). High-frequency social media users were more likely to agree that "social media is useful for managing my IBD, " compared with low-frequency social media users (OR 3.23, 0.3–10.1, P = 0.199). Fifty-five percent of respondents were interested in obtaining patient-with-IBD education through social media, or organizations such as the CCFA, whereas 45% did not express interest. Sixty-two percent of patients would be interested in following a social media account established by their gastroenterologist. Privacy and/or confidentiality issues were the primary barriers to social media use. Last, most patients were unsure of the quality of IBD information posted online. Conclusions: The results of this study suggest that patients who frequently use social media are highly interested in using social media in the management of their IBD. Most patients with IBD in our study were interested in receiving IBD information from their gastroenterologist and other patient-related organizations through social media. Most patients are unsure of the quality of IBD information posted on social media. Gastroenterologists should be aware that their patients may use social media to obtain disease education. Future studies should assess the quality of IBD information on social media and the effectiveness of communication through social media as a means to improve patient education and outcomes. Abstract : Article first published online 12 October 2016.